Lobato, Mirta Zaida, Historia de las trabajadoras en la Argentina (1869-1960), Buenos Aires, Edhasa, 2007 - SILVANA PALERMO (H-Industri@)
Lobato, Mirta Zaida, Historia de las trabajadoras en la Argentina (1869-1960), Buenos Aires, Edhasa, 2007